T210. REVIEW OF USE OF ADJUNCTIVE PSYCHOSTIMULANTS IN PATIENTS WITH SCHIZOPHRENIA: A RETROSPECTIVE STUDY. (18th May 2020) - Zhand, Naista; Osborne, Roisin; Stuyt, Marika; Hatko, Anna; Labelle, Alain
Abstract: Background: Augmentation with psychostimulants has been postulated as one of the potential treatment options for negative and/or cognitive symptoms of schizophrenia. However, the major drawback for use of these agents is a potential risk of relapse or worsening of psychosis through direct or indirect dopamine agonism activity. Therefore a great deal of caution is required when using stimulants in individuals with psychosis. The present study aims to review the rate of adjunct psychostimulant prescription, and their efficacy and safety in a real life setting. Furthermore, we intend to compare the efficacy of psychostimulants when added to clozapine compared to other antipsychotics. Data was obtained from a schizophrenia outpatient clinic, in a tertiary care centre in Canada. Methods: A chart review was conducted on outpatients enrolled in the schizophrenia program at the Royal Ottawa Mental Health Centre, between 31/5/2014 - 1/6/2019. For patients who were prescribed any psychostimulants at any time point up to 3-months prior to the study end date, clinical information related to efficacy and tolerability of stimulants, psychotic symptoms and concomitant antipsychotic treatment was collected. Results: A total number of 1300 patients were included in the chart review study. Of those, 80 patients (6.15%) were prescribed stimulants during the study period. Of the participants who prescribed stimulants, 70% were male, 17.5% had a diagnosis of ADHD, and 38.75% were on clozapine. 21.25% had more than one trial of stimulant medications. Over half of participants continued on stimulants during the study period, with an overall good response in 36.25%, and minimal or equivocal response in 20% of participants on stimulants. Stimulants were discontinued in 13.75% of patients due to lack of efficacy, and 30% due to problematic symptoms. The data is currently being analysed; Comprehensive results to follow. Discussion: The preliminary results indicate that the use of stimulants was associated with improvement in cognitive and/or negative symptoms in a subset of patients and resulted in worsening of psychosis in some patients. The authors will discuss the efficacy and tolerability of use of adjunctive stimulants in outpatients with schizophrenia. Potential factors associated with the observed response and side effects will be discussed further.